Eficiência na absorção e utilização do fósforo em clones de Eucalyptus spp. - Aguilar, Marcos Vinícius Miranda (2025)
Eucalyptus clones with higher phosphorus (P) uptake efficiency are able to grow in soils with lower P availability due to their rapid growth and biomass production. These characteristics favor the reduction of the use of phosphate fertilizers in nurseries and cultivation areas, and at the same time reduce the cost of inputs and the probability of soil contamination with P. However, commercially used eucalyptus clones with higher P uptake efficiency are still relatively unknown. Thus, the objective of this study was to investigate whether morphological, physiological, and biochemical characteristics of eucalyptus plants influence the nutritional efficiency of P and cause differences in plant growth. In addition, we sought to select eucalyptus clones that are more efficient in the use and uptake of P. Therefore, this research was subdivided into two studies, where the efficiency in the uptake and use of phosphorus (P) in the clones E. saligna, E. urograndis, and E. dunnii were evaluated. In Study 1, the kinetic parameters of P uptake were evaluated using a hydroponic system. In Study 2, the P-efficient clones selected in the hydroponic studies were grown in pots with soil with low P levels to verify whether they maintain the P efficiency characteristics observed in the hydroponic system. The experiments were conducted in a completely randomized design, with two P levels (high P and low P) and three Eucalyptus spp. clones (E. saligna, E. urograndis, and E. dunnii), with six replicates per treatment in both studies. Morphological parameters of the shoots and root systems, biomass production, photosynthetic variables, chlorophyll a fluorescence, photosynthetic pigments, antioxidant enzyme activity and oxidative stress indicators, as well as P concentrations in tissues were evaluated in both studies. However, only in study 1 were the kinetic parameters (Vmax, Km, Cmin and I) evaluated. In study 1, the clones E. saligna and E. urograndis were more efficient in P absorption, since they presented the lowest Km and Cmin values, greater biomass and P accumulation in tissues, allowing P absorption even at low concentrations. E. dunnii showed the highest Km and Cmin for P, lowest biomass and P accumulation in tissues, indicating adaptation to environments with higher P availability. In study 2, E. urograndis and E. saligna also showed greater P efficiency, as they did not present limitations in photosynthetic rate and biomass in low P. E. dunnii accumulated less P in roots and metabolism was negatively affected in soils with low P and, therefore, does not present efficiency in P use, requiring greater P availability. On the other hand, E. urograndis and E. saligna can grow in environments with low P levels.